Transcription factors link mouse WAP‐T mammary tumors with human breast cancer. Issue 6 (13th December 2012) - Otto, Benjamin; Streichert, Thomas; Wegwitz, Florian; Gevensleben, Heidrun; Klätschke, Kristin; Wagener, Christoph; Deppert, Wolfgang; Tolstonog, Genrich V.
Abstract Mouse models are important tools to decipher the molecular mechanisms of mammary carcinogenesis and to mimic the respective human disease. Despite sharing common phenotypic and genetic features, the proper translation of murine models to human breast cancer remains a challenging task. In a previous study we showed that in the SV40 transgenic WAP‐T mice an active Met‐pathway and epithelial‐mesenchymal characteristics distinguish low‐ and high‐grade mammary carcinoma. To assign these murine tumors to corresponding human tumors we here incorporated the analysis of expression of transcription factor (TF) coding genes and show that thereby a more accurate interspecies translation can be achieved. We describe a novel cross‐species translation procedure and demonstrate that expression of unsupervised selected TFs, such as ELF5, HOXA5 and TFCP2L1, can clearly distinguish between the human molecular breast cancer subtypes—or as, for example, expression of TFAP2B between yet unclassified subgroups. By integrating different levels of information like histology, gene set enrichment, expression of differentiation markers and TFs we conclude that tumors in WAP‐T mice exhibit similarities to both, human basal‐like and non‐basal‐like subtypes. We furthermore suggest that the low‐ and high‐grade WAP‐T tumor phenotypes might arise from distinct cells of tumor origin. Our results underscore the importance of TFs as common cross‐species denominators in the regulatory networks underlying mammary carcinogenesis.